Utilização do bagaço da cana-de-açúcar, água de maceração de milho e farinha da casca de maracujá para a produção de celulases pelo termofílico Bacillus sp. SMIA-2 - Fernandes, Raquel Nunes (2016)
The use of agroindustrial residues as carbon sources for obtaining enzymes, has ensured good enzyme production and reduction of process costs. In this context, this study has as goal evaluated the growth of the thermophilic Bacillus sp. SMIA-2 and enhance the secretion of cellulase in submerged crops containing alternative and cheap substrates such as sugarcane bagasse, corn steep liquor and passion fruit peel flour. By studying the different types of bagasse it was observed that the best specific activity levels of avicelase and FPase were obtained when using the residue that treated with potassium hydroxide. The optimal cultivation condition, determined using the technique of the central composite design (23 ), was 0.625% (w/V) sugarcane bagasse, 0.625% (w/V) of corn steep liquor and 120 hours incubation time for CMCase and 168 hours for avicelase. The addition of new carbon sources of the medium showed that the microorganism was able to satisfactorily use each one of them, but the activities of cellulolytic enzymes has varied depending on the sources tested. An inhibition of enzymatic synthesis in medium containing cellobiose was observed. However, a large increase in the secretion of the cellulase was obtained with the flour of passion fruit peel, sugarcane bagasse and corn steep liquor, showed specific activity values of 3.931 U.mg protein-1 for avicelase, 1.032 U.mg protein-1 for CMCase and 4.084 U.mg protein-1 for FPase. Similar levels were measured in media containing apple pectin. The maximum production of the enzymes was observed in the range 168 hours, when the culture was in stationary phase. The study of the effect of flour concentrations of passion fruit peel indicated that addition of 0.5 % (w/V) and 0.75 % (w/V) of this substrate in the middle equally provided better production of cellulases. As an overview of this study, it was possible to increase the production of cellulases by optimizing the culture medium.